UV to submillimetre luminosity functions of TNG50 galaxies - Trčka, Ana; Baes, Maarten; Camps, Peter; Kapoor, Anand Utsav; Nelson, Dylan; Pillepich, Annalisa; Barrientos, Daniela; Hernquist, Lars; Marinacci, Federico; Vogelsberger, Mark (Monthly notices of the Royal Astronomical Society, 2022)
We apply the radiative transfer (RT) code skirt on a sample of ∼14000 low-redshift (z ≤ 0.1) galaxies extracted from the TNG50 simulation to enable an apples-to-apples comparison with observations. The RT procedure is calibrated via comparison of a subsample of TNG50 galaxies with the DustPedia observational sample: we compare several luminosity and colour scaling relations and spectral energy distributions in different specific SFR bins. We consistently derive galaxy luminosity functions for the TNG50 simulation in 14 broad-band filters from UV to submillimetre wavelengths and investigate the effects of the aperture, orientation, radiative transfer recipe, and numerical resolution.
Gesehen am 07.11.2023